Identificação dos fatores críticos ao adequado funcionamento das secretarias administrativas de programas de pós-graduação em uma IFES - Kawamura, Luciana Missae (Universidade Federal de São Carlos, 2019)
Some factors are fundamental for the success of an organization and knowing these factors can help the management in the elaboration of a strategic planning in search of better results. The stricto sensu graduate programs are constantly evaluated and their results will determine their success and their permanence in the National Graduate System. The evaluation is carried out every four years based on annual reports that the programs send to CAPES. Completion of the PPG report is carried out through a platform where qualitative and quantitative data are informed regarding the program proposal, teachers, students, intellectual production and social insertion. The responsibility for the data informed is of the Coordination of the PPG, however, the collection, systematization and insertion of data in the platform are done in most cases with the support of the secretariat. Faced with this, knowing the critical success factors of post-graduate departments becomes relevant to assist in the preparation of an adequate annual report. The objective of the research was to identify the critical factors related to the individual and collective competences of the occupants of the function of post-graduate secretaries linked to a Science Center, a federal public university, that contribute to the program. For this, the critical success factors of the graduate programs were raised through the reading of the area documents and the evaluation reports of the programs, and it was sought to know the vision of the current occupants of the secretaries function from interview semi-structured on the functioning of the secretariat, knowledge, skills and attitudes existing and to be developed, strategic planning, evaluation and key critical factors to serve as secretary of PPG. The approach used was people management by competencies. Based on the results obtained, a set of actions was elaborated aiming at improvements in the processes of the secretariats and in the completion of the annual report and consequently search for better results for the program. The results have identified that the servers are committed to the function, have the necessary skills and abilities and that the greatest difficulty is in the volume of activities and in dealing with people. The secretariat is usually the place where the demands and complaints are concentrated, so the secretaries should be proactive, ethical, and have a good relationship with teachers, students and general public. Among the suggested actions are: promotion of face-to-face events or meetings with the participation of the post-graduate secretaries that allow the exchange of information and experiences; sharing of information and clarification of doubts whenever there is a change in procedures; offerings of training or discussion meetings that provide the improvement of the knowledge and skills of the secretaries and search for improvement of the processes that involve the secretary; sharing of the strategic plan of the program with the secretariats; hours, during periods of important demands, so that the secretariat can prioritize these activities.
Identification of the critical success factors in the administrative secretaries of post-graduate programs in an IFES
Keywords: Gestão por competências; Planejamento estratégico; Ensino superior; Fatores críticos de sucesso em Programas de Pós-Graduação; Management by competences; Strategic planning; Higher education; Critical success factors in postgraduate programs; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA